Ratusz jako przestrzenne i prawne centrum rozwoju miasta. Rozważania i odniesienia do badań w Niemczech i Austrii od 1990 roku - Opll, Ferdinand (Roczniki Dziejów Społecznych i Gospodarczych, 2014)
The Town Hall as the focus of the spatial and political system in the city’s development: considerations and references to relevant German and Austrian research since 1990 (Summary) The article starts with the analysis of respective definitions and considerations regarding the term Rathaus in different languages (German, Italian, English and French). Subsequently the origins of town-halls are taken into closer consideration, a topic which – seen from the standpoint of modern city-marketing – plays a decisive role for the “ranking” of towns. As a synonym for the evolution of civic and urban liberties in Italy as well as north of the Alps the chronology of the evolution of town-halls as well as their topographical placement within the urban pattern are of greatest importance. More explicit considerations are given with regard to town-halls in Austrian towns. An excellent basis for this analysis is the data provided by the series of more than 60 volumes of the Österreichischer Städteatlas (edited 1982–2013). In the end an overview to the respective research with hints to some deficits and possibilities for further investigation is given. It should especially be indicated that the “Rathaus”-topic can and should play a much greater role within actual trends of research (“spatial turn”).